2005
DOI: 10.1523/jneurosci.2005-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Calcium/Calmodulin-Dependent Protein Kinase II Alters Structural Plasticity and Cytoskeletal Dynamics inDrosophila

Abstract: Drosophila dendritic arborization (da) neurons contain subclasses of neurons with distinct dendritic morphologies. We investigated calcium/calmodulin-dependent protein kinase II (CaMKII) regulation of dendritic structure and dynamics in vivo using optically transparent Drosophila larvae. CaMKII increases the dynamic nature and formation of dendritic filopodia throughout larval development but only affects neurons that normally contain dendritic filopodia. In parallel, we examined the effects of Rac1 activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
82
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(93 citation statements)
references
References 72 publications
10
82
0
1
Order By: Relevance
“…It is particularly important to identify sensory cell target genes of Ss and other transcription factors; ideally, it would be useful to profile the complement of target genes specific for each sensory neuron. Additionally, generating complex dendritic patterns will also require localizing RNAs and proteins at specific defined sites along processes, and understanding how their functions can be modified at these defined sites (Andersen et al 2005). Connecting molecular genetics with dendrite morphology will require a strong dose of cell biology.…”
Section: Discussionmentioning
confidence: 99%
“…It is particularly important to identify sensory cell target genes of Ss and other transcription factors; ideally, it would be useful to profile the complement of target genes specific for each sensory neuron. Additionally, generating complex dendritic patterns will also require localizing RNAs and proteins at specific defined sites along processes, and understanding how their functions can be modified at these defined sites (Andersen et al 2005). Connecting molecular genetics with dendrite morphology will require a strong dose of cell biology.…”
Section: Discussionmentioning
confidence: 99%
“…Achaete is a bHLH transcription factor required for SOP specification within proneural equivalence groups (see Introduction). We compared the pattern of Achaete expression in sr.AmunTRFP nota with that in control nota using sr.mRFP (a myristylated monomeric RFP; Andersen et al 2005). Achaete-positive cells are detected in regions of control nota expressing mRFP at 9 hr APF ( Figure 8A).…”
Section: ; Muller Et Al 2005) Ep(x)1503 a Uas-containing Transmentioning
confidence: 96%
“…In mammalian development, following dendrite outgrowth and branching, numerous F-actin-rich structures, including dendritic spines and dendritic filopodia (Fifkova and Delay 1982), form and continuously emerge and retract on dendrites. Previously, we demonstrated that actin-rich dendritic filopodia can also be found on Drosophila dendrites during larval stages and that these structures also continuously emerge and retract on dendrites (Andersen et al 2005). Forward genetic analysis of late stages of dendrite development have been limited because many assay systems used to analyze dendrite development examine neurons that lack actin-rich dendritic filopodia or dendritic spines on mature dendrites (Wu and Cline 1998).…”
mentioning
confidence: 99%